Projeto perspectiva: manifestações culturais, artísticas e interação há 22 anos no câmpus de Bauru - Barros, Luiz Felipe de Oliveira [UNESP]; Oliveira Neto, Luttgardes de [UNESP]; Lima, Marlene de Souza Almeida [UNESP]; Cerigatto, Jorge Guilherme [UNESP]; Alves, Gabriela; Nayadi, Fernanda (Universidade Estadual Paulista (Unesp), 2015)
Since 1993, the Perspective Project brings to Bauru’s Unesp campus several kinds of cultural and artistic manifestations, with the purpose of enrich the knowledge of their students and increase the tolerance and respect about different cultures that coexists inside of UNESP campus in Bauru. Beside this public sphere, the Perspective Project aims to structure their presentations based on context of Bauru’s communities and all national territory, in general.

Desde 1993 o Projeto Perspectiva traz ao campus da UNESP de Bauru diferentes tipos de manifestações artísticas e culturais, com o intuito de enriquecer o saber de seus estudantes e ampliar a tolerância e respeito às diversas culturas presentes dentro da UNESP de Bauru. Além desse universo público, o Projeto Perspectiva também pretende estruturar as apresentações com base no contexto das comunidades bauruenses e de todo território nacional em geral.
Keywords: Culture; Art; Knowledge